Coronary artery bypass graft surgery in dialysis patients - Jahangiri, M. (1997)
Objective—To examine the short term results and long term survival of patients on long term dialysis undergoing coronary artery bypass graft surgery. Methods—A retrospective analysis of 19 patients on established dialysis who underwent coronary revascularisation between 1983 and 1995; 14 patients (73%) had class IV angina and five (25%) had unstable angina requiring heparin and nitrate infusions before surgery. Results—The 30 day mortality was 5%. Follow up was completed in the remaining 18 patients. The mean follow up time was 34 months (range eight to 61). During the follow up period four patients died of cardiac causes. The actuarial survival at one, two, and three years was 87%, 78%, and 59%, respectively. The overall functional status was significantly improved compared to preoperative levels, with a mean Karnofsky score of 76% (p < 0.01) at three years. Conclusions—Coronary artery bypass graft surgery can be performed with increased but acceptable morbidity and mortality in chronic dialysis patients. It results in considerable improvement in symptoms and functional status. However, long term survival is limited and this requires further investigation.   Keywords: coronary artery bypass graft surgery;  dialysis